Strategies to Introduce Topographical and Structural Cues in 3D‐Printed Scaffolds and Implications in Tissue Regeneration. Issue 12 (27th October 2021) - Iturriaga, Leire; Van Gordon, Kyle D.; Larrañaga-Jaurrieta, Garazi; Camarero‐Espinosa, Sandra
Abstract : Regeneration of tissues represents a current challenge and a need to treat damage and diseased organs, and is becoming determinant to alleviate the burden of healthcare systems with the increasing age of the population. Although many strategies are being developed and some scaffolds are already reaching the market, issues of formation of well‐structured and functional tissues are still prevalent. Additive manufacturing and particularly 3D printing have emerged as ideal technologies to fabricate patient‐specific scaffolds and allow for the easy modification of multiple structural parameters. Yet, these are generally composed of smooth fibers that are not able to drive, by themselves, the formation of well‐structured tissues. The use of physical cues to modulate cellular processes such as migration, proliferation, differentiation, and matrix synthesis has been proven effective in 2D. Thus, the extrapolation of these physical cues to 3D‐printed scaffolds appears as a tempting approach to promote the formation of functional tissues and thus, many strategies are being developed to this end. Herein, an overview of developed techniques to introduce topography and porosity to 3D‐printed scaffolds and their effect on the cell response and tissue formation is provided. Abstract : Herein, the latest advances in additive manufacturing technologies that allow patterning of topographical and structural cues that serve to control cell functions and ultimately the regeneration of specific tissues are highlighted. A special focus is given to the knowledge previously generated in 2D systems of the mechanisms of cell mechanosensing and mechanotransduction.